Effect of rhizosphere bacteria on germination and growth of bell pepper Capsicum annuum L. var. Cacique Gigante (Bioagro, 2020)
Inoculation with plant growth promoting rhizobacteria (PGPR) represents an alternative to increase the germination and improve the production of horticultural crops. In  this  study  the  effect  of  six  rhizosphere  bacterial  isolates native to Merida, Venezuela was evaluated over the germination of bell pepper var. Cacique Gigante. Then, the best four isolates were selected to evaluate the effect on plant growth. A phosphate solubilization test was performed and the production of AIA was determined with three concentrations of tryptophan (0.025, 0.05, and 0.1 mg∙L-1). The germination test was performed in Petri dishes under aseptic conditions, inoculating the disinfected seeds with 108 UFC∙mL-1 of each strain at 28 °C in the dark. Growth was evaluated in vitro in MS medium with or without tryptophan (0.05 mg∙L-1) at 25 °C with 16/8 hours light/dark. As a result, all strains solubilized Ca3(PO4)2, and the Leu2A(1)2, YAC1, Nod2R and ME01 rhizobacteria produced IAA, with and without tryptophan. Seeds that after storing had a viability decreased from 98 to 75 % were stimulated by the rhizobacteria, increasing germination 13-23 %. In addition, they accelerated in one day the maximum germination with respect to the control. After 55 days of growth, there were increases in length and dry weight of root and stem inoculated with YAC1 and Leu2A(1)2, and with application of tryptophan. It was demonstrated that inoculation of bell pepper seeds with rhizobacteria, especially with Leu2A(1)2, represents an alternative to increase germination and growth of the plant.
Keywords: Azospirillum; IAA; phosphate solubilization; rhizobia